Blue Spaces as Resources for Health and Wellbeing: Survey Comparisons of Indoor and Outdoor Settings from Ireland - McNamara, Maedhbh; Murphy, Ailise; Dowler, Fiona; Foley, Ronan (Revista de Estudios Andaluces, 2020)
There has been an upsurge of recent interest in blue spaces, especially evident in nature-based research associated with the health and wellbeing potential of oceanic, coastal and inland waters. This paper documents Irish studies that compare indoor and outdoor blue spaces for different user communities and practices. The studies employ qualitative methodologies including interviews, visual surveys and go-alongs, to enact a form of ‘place capture’ in three different types of blue space. The first study, based at an indoor swimming pool in West Dublin, identifies the benefits and value of swimming as a healthy practice, from three different cohorts of respondents (n=79). The second study of a single canal space in the Midlands looks at the benefits identified by mixed regular users, including Park Runners, of the blue-ways alongside the Royal Canal (n=12). A third study captured comparative in-situ user-perspectives from two very different blue spaces, canal and beach, in two locations in Central/South Dublin (n=8). What emerges from the studies are complex assemblages of identified therapeutic outcomes in both health and wellbeing terms, reflecting diverse user perspectives from different types of blue space. The accounts reflect the literature in identifying both health-promoting and health-reducing dimensions of blue space experience, as well as commonalities and variations in how users explicitly value blue spaces settings. Key additional themes include, self-discovery, socialisation and recovery that hint at the potential of qualitatively focused ‘emplaced blue community’ studies to underpin and inform public health policy and promote health resilience in Ireland and beyond.